Loss of ileal IgA(+) plasma cells and of CD4(+) lymphocytes in ileal Peyer's patches of vitamin A deficient rats - BJERSING, J L (Blackwell Science Inc, 2002)
Child mortality in diarrhoeal disease is increased significantly by vitamin A deficiency in poor countries. The pathological mechanisms are not known in detail. However, in this paper we report that vitamin A-deficient Wistar rats had much reduced IgA(+) plasma cells in the ileal lamina propria (eightfold reduction from 470 cells/mm(2), P = 0·009), as well as a prominent reduction of CD4(+) cells in the parafollicular regions of ileal Peyer's patches (reduction from 7200 to 105 cells/mm(2), P = 0·009). IL-2Ralpha-chain (CD25) positive lymphocytes in the ileal Peyer's patches were also reduced significantly in vitamin A deficiency (from 1400 to 300 cells/mm(2), P = 0·009). The density of CD8 cells tended to be increased relative to the control animals (from 5100 to 6000 cells/mm(2), not statistically significant). In conclusion, the marked decrease of lamina propria IgA(+) plasma cells may be one cause of the high diarrhoeal mortality in vitamin A deficiency. This, in turn, appears to be related to reduced numbers of activated or regulatory CD4(+) T cells in Peyer's patches.